An in-Vitro Comparative Study to Evaluate Effect of Different Irrigation Activation Methods in Penetrating into Simulated Lateral Canals in Root Canal System (Journal of Hama University, 2021)
Aim of Study: to evaluate the penetration of irrigant solution into simulated lateral canals using different irrigation activation techniques, preparing them for obturation.Materials and Methods: Thirthy intact, completey developed uni-radicular teeth were instrumented and prepared up to F2 file, crowns were separated from roots and three simulated lateral canals were created at 2mm ,4mm and 6mm levels from the root apex. Teeth were randomly divided into 3 groups (n=10): Group I: activation with reciprocation movement. Group II: passive ultrasonic irrigation (PUI). Group III: control group without activation. Teeth were obturated using single cone and bioceramic sealer. Sealer penetration into simulated lateral canals was evaluated using digital x-ray and sensor then teeth were cleard to be evaluated under endo-microscope. Mann-Whitney test was applied to verify diffences between the studied groups in sealer penetration rate into simulated lateral canals.Conclusion: sealer penetration into simulated laterals canals was the lowest in the control group. Also, irrigation activation with reciprocation movement provides better penetration into middle and apical lateral canals than passive ultrasonic activation. (P